Translating Tenor: With Reference to the English Versions of Hong Lou Meng - Liu, Zequan (Meta, 2008)
AbstractThe objective of this paper is to see how the Chinese tenor as exhibited by the use of titles and honorifics in the classic novel Hong Lou Meng is translated in its five English versions. I shall compare the translations of several dialogues from the novel with special reference to the tenor-markers. By adopting House’s interpersonal equivalence as a criterion to measure the social distance and power between the dyads as shown by the tenor in both the SL conversations and their respective TL versions, I shall investigate the relationship between the interpersonal equivalence that is acquired in the TT and the strategies that are adopted to translate the dialogues. The argument put forward here is that in order to produce a translation that not only reads fluently but also retains the linguistic and cultural features of a foreign literary work, foreignising should be adopted as a mainstream rather than exclusive strategy, with assistance drawn from domesticating solutions.